PENGARUH FRAUD STAR TERHADAP FINANCIAL STATEMENT FRAUD DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017 - 2020) - Jojor Lamria Situmorang; Sukrisno Agoes (Fakultas Ekonomi Universitas Tarumanagara, 2025)
This research aims to determine how fraud stars are: pressure, opportunity, rationalization, capability, and integrity of financial statement fraud with audit quality as a moderation variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The sample was selected by purposive sampling method and valid data is financial statement data as the selected sample for the 2017-2020 period amounted to 144 (one hundred forty four) manufacturing companies listed on the Indonesia Stock Exchange (IDX). The data processing technique uses multiple regression analysis assisted by the Eviews program. The results of this study show that the element of influence of fraud star on financial statement fraud using the Beneish M-Score model with audit quality with moderation variables described as follows, namely: pressure does not negatively affect financial statement fraud, opportunity and rationalization have a positive effect on financial statement fraud, capability does not have a positive effect on financial statement fraud, integrity has a negative effect on financial statement fraud, audit quality does not weaken the negative influence of pressure on financial statement fraud, audit quality weakens the positive influence of opportunity on financial statement fraud, audit quality does not weaken the negative influence of rationalization and capability on financial statement fraud, and audit quality reinforces the positive influence of integrity on financial statement fraud. The implication of this research is the need to use fraud detection tools, one of which is fraud star, which is a tool to detect financial statement fraud that can help investors in analyzing to provide information on the financial condition of companies to be invested in companies and the use of external audit quality implementation of financial statements is needed to avoid misstatement financial statements and also for potential investors about the use of the Beneish M-Score model in financial statements to predict whether the company category is a manipulator or not so that it requires more in-depth analysis in decision making